What happened to discrete chaos, the Quenouille process, and the sharp Markov property?: some history of stochastic point processes - Guttorp, Peter; Thorarinsdottir, Thordis (International statistical review, 2012)
The use of properties of a Poisson process to study the randomness of stars is traced back to a 1767 paper. The process was used and rediscovered many times, and we mention some of the early scientific areas. The name Poisson process was first used in print in 1940, and we believe the term was coined in the corridors of Stockholm University some time between 1936 and 1939. We follow the early developments of doubly stochastic processes and cluster processes, and describe different efforts to apply the Markov property to point processes.